The path : what Chinese philosophers can teach us about the good life - Puett, Michael J., 1964- (Simon & Schuster, 2016)
"Why is a course on ancient Chinese philosophers one of the most popular at Harvard? It's because the course challenges all our modern assumptions about what it takes to flourish. This is why Professor Michael Puett says to his students, The encounter with these ideas will change your life. As one of them told his collaborator, author Christine Gross-Loh, You can open yourself up to possibilities you never imagined were even possible. These astonishing teachings emerged two thousand years ago through the work of a succession of Chinese scholars exploring how humans can improve themselves and their society. And what are these counterintuitive ideas? Good relationships come not from being sincere and authentic, but from the rituals we perform within them. Influence comes not from wielding power but from holding back. Excellence comes from what we choose to do, not our natural abilities. A good life emerges not from planning it out, but through training ourselves to respond well to small moments. Transformation comes not from looking within for a true self, but from creating conditions that produce new possibilities. In other words, [this book] upends everything we are told about how to lead a good life. Above all, unlike most books on the subject, its most radical idea is that there is no path to follow in the first place-- just a journey we create anew at every moment by seeing and doing things differently. Sometimes voices from the past can offer possibilities for thinking afresh about the future"